Treatment adherence of diabetes mellitus patients: Is it affected by demographic and patient-related factors? A literature review - Paraskevi Theofilou (Academia Medicine)
The importance of adherence to treatment is very high. The main purpose of this study was to investigate the adherence of patients with diabetes mellitus to their treatment. For this purpose, a systematic review was carried out, where relevant studies were searched in the PubMed and Google Scholar databases with specific keywords, and, subsequently, the most appropriate studies were selected (based on specific inclusion/exclusion criteria) and analyzed. In total, from the literature search, 16 studies were identified. Based on these studies, patients with diabetes mellitus show quite low adherence to insulin therapy. The perceptions about the disease of diabetes, the availability of drugs, the diabetes education provided, perceptions of medication, current patients’ employment, younger age, educational level, nationality, HbA1c levels, abstinence from alcohol, presence of peripheral vascular disease, income, keeping their appointments in primary health care, and the religious beliefs about healing and healing practices are important factors influencing the compliance of patients with diabetes in their treatment. Adherence of patients with diabetes mellitus to treatment is an extremely important issue for them since the lack of it negatively affects not only the health of patients but also their quality of life.